2018
DOI: 10.1002/jcp.27602
|View full text |Cite
|
Sign up to set email alerts
|

Meldonium improves Huntington’s disease mitochondrial dysfunction by restoring peroxisome proliferator‐activated receptor γ coactivator 1α expression

Abstract: Mitochondrial dysfunction seems to play a fundamental role in the pathogenesis of neurodegeneration in Huntington’s disease (HD). We assessed possible neuroprotective actions of meldonium, a small molecule affecting mitochondrial fuel metabolism, in in vitro and in vivo HD models. We found that meldonium was able to prevent cytotoxicity induced by serum deprivation, to reduce the accumulation of mutated huntingtin (mHtt) aggregates, and to upregulate the expression of peroxisome proliferator‐activated receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…To confirm the efficacy of newly synthesized compounds in vivo, the selected compounds were tested in a Drosophila model of HD, with transgenic flies that express full-length human pathogenic cDNA, encoding a mutated HTT protein [ 9 , 24 ]. The expression of this construct in the transgenic fly recapitulated the majority of the pathological hallmarks of HD, including early death and locomotor dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To confirm the efficacy of newly synthesized compounds in vivo, the selected compounds were tested in a Drosophila model of HD, with transgenic flies that express full-length human pathogenic cDNA, encoding a mutated HTT protein [ 9 , 24 ]. The expression of this construct in the transgenic fly recapitulated the majority of the pathological hallmarks of HD, including early death and locomotor dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of this construct in the transgenic fly recapitulated the majority of the pathological hallmarks of HD, including early death and locomotor dysfunction. In a recent previous work, Di Cristo et al reported that THP significantly improved the lifespan and motor function in this HD fly and that the srl gene (DmPGC1-alpha) was involved in those effects [ 9 ]. In this work, we wanted to evaluate the lifespan and motor dysfunction of Q128HD-FL flies after treatment with the THP-derived molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe loss of mitochondrial activities, such as reduction in the activities of complex II/III and aconitase, was found in postmortem samples of the caudate/putamen in HD patients [15]. However, defects in mitochondrial mass are not very common in HD animal models and were found only in selected models [16][17][18].…”
Section: Excessive Mitophagy In Peripheral and Nervous System Defectsmentioning
confidence: 99%